First-time home buyers : factors influencing decision making / Lizawati Abdullah ... [et al.] - Abdullah, Lizawati; Mohd Nor, Ilyana Bazlin; Jumadi, Norhaslina; Arshad, Huraizah (2012)
In a housing market, first time house buyers are important as they indirectly act as indicator to help regulating the housing policies and further promoting home ownership. The preferences of this group are taken into consideration as the basis for forecasting housing demand. Therefore, this group is considered as important and it is essential to identify their preferences. Purchasing a home is considered as the biggest financial decision in one's life and would affect the household's budget as the process involves a long time commitment starting from the very first down payment to the monthly payment in the future. Based on the literature reviews, several factors have been recognized which may influence their decision-making. Among the factors are house price, location, family transition, neighborhood and others. In this paper, the emphasis is placed on identifying the most important factors that influenced their decision.